Fine-Mapping of the PLCL2 Gene Identifies Candidate Variants Associated With Ischaemic Stroke Risk in Metabolic Syndrome Patients - Huang, Xiaoya; Ye, Qiang; Zhang, Yanlei; Chen, Yanyan; Li, Jia; Sun, Jun; Ye, Zusen (Frontiers in Neurology, 2022)
A genome-wide association study (GWAS) reported PLCL2 on chromosome 3p24.3 (rs4618210:A>G) as a novel susceptibility locus for myocardial infarction in the Japanese population. As the most common pathological process, atherosclerosis leads to metabolic syndrome (MetS)-related ischaemic stroke (IS) and myocardial infarction. Hypothesizing that polymorphisms of the PLCL2 gene might be associated with the onset and prognosis of IS in MetS patients, we performed the following study in a Chinese Han population. A total of 709 cases (patients with MetS plus IS) and 711 controls (patients with MetS) were enrolled. A fine-mapping strategy was adopted to identify tagged single nucleotide polymorphisms (SNPs) of the PLCL2 gene, and improved multiplex ligation detection reaction (iMLDR) technology was used to genotype the selected SNPs. Logistic regression was used to analyse the values of the selected SNPs for the risk of IS between the cases and controls, adjusting for sex, age, hypertension, dyslipidaemia, hyperglycaemia, smoking and drinking. To compare the mean age of IS onset among different risk score groups, a genetic risk score was constructed for each case. The cumulative risk of IS events in the case group was presented using a cumulative incidence curve. All cases were followed up for 3 months, and functional outcomes were recorded prospectively. Two SNPs (rs4685423 and rs4618210) were significantly related to the risk of IS in MetS patients. For rs4685423, patients who were AA homozygotes were less likely to suffer from IS than C-allele carriers (OR 0.718; 95% CI 0.567–0.909; multivariate-adjusted, P = 0.006). For rs4618210, A-allele carriers were less likely to develop IS than patients who were GG homozygotes (OR 0.679; 95% CI 0.548–0.841; multivariate-adjusted, P < 0.001). As the genetic risk score increased, the mean age at IS onset decreased (log-rank P = 0.010). There was no statistically significant difference in the distribution of the 90-day modified Rankin Scale (mRS) outcomes across the rs4685423 (P = 0.319) or rs4618210 polymorphisms (P = 0.148). Our findings suggested that genetic polymorphisms of PLCL2 might be associated with the onset of MetS-related IS. Further studies are warranted to validate our findings in other ethnic populations.